1997
DOI: 10.1007/s004420050301
|View full text |Cite
|
Sign up to set email alerts
|

Importance of dietary nitrogen and carbohydrates to survival, growth, and reproduction in adults of the grasshopper Ageneotettix deorum (Orthoptera: Acrididae)

Abstract: Key demographic traits in insect herbivores (survival, growth, and egg production) are often responsive to variation in diet quality, especially to dietary nitrogen (N) levels. Soluble carbohydrates may also be limiting. Using defined diets under controlled laboratory conditions, we examined survival, growth, and egg production in response to a range of diet qualities in adult females of a grass-feeding grasshopper Ageneotettix deorum (Scudder). Diets varied factorially within naturally occurring ranges of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 38 publications
11
105
1
3
Order By: Relevance
“…When not provided with a choice of foods, both sexes prioritized protein and carbohydrate intake over phosphorus intake, whereas protein and carbohydrate intake were both regulated relatively equally (figure 2b, convex arc intake array; sensu [5]), with a decrease in intake evident with the lowest P : C foods. Similar to previous studies [10,22,37], we demonstrated that G. veletis cannot simultaneously maximize all fitness traits, and thus experienced trade-offs between fitness traits depending on the nutritional composition of available foods. Adult weight gain and egg production were maximized on high-protein diets (3 P : 1 C ), whereas adult lifespan was maximized on high-carbohydrate diets (males: 1 P : 3 C ; females: 1 P : 8 C ) and acoustic mate signalling effort was maximized with increased food intake regardless of nutrient ratio.…”
Section: Discussion (A) Experiments 1: Influence Of Dietary Nutrient Bsupporting
confidence: 88%
“…When not provided with a choice of foods, both sexes prioritized protein and carbohydrate intake over phosphorus intake, whereas protein and carbohydrate intake were both regulated relatively equally (figure 2b, convex arc intake array; sensu [5]), with a decrease in intake evident with the lowest P : C foods. Similar to previous studies [10,22,37], we demonstrated that G. veletis cannot simultaneously maximize all fitness traits, and thus experienced trade-offs between fitness traits depending on the nutritional composition of available foods. Adult weight gain and egg production were maximized on high-protein diets (3 P : 1 C ), whereas adult lifespan was maximized on high-carbohydrate diets (males: 1 P : 3 C ; females: 1 P : 8 C ) and acoustic mate signalling effort was maximized with increased food intake regardless of nutrient ratio.…”
Section: Discussion (A) Experiments 1: Influence Of Dietary Nutrient Bsupporting
confidence: 88%
“…These nitrogen losses are often a major constraint on growth and reproduction ( Joern & Behmer 1997), so that symbioses for recycling nitrogenous waste products have evolved in a number of lineages, e.g. yeasts in planthoppers (Sasaki et al 1996), intracellular flavobacteria (Blattabacterium sp.)…”
Section: Discussionmentioning
confidence: 99%
“…protein) and an energy source (i.e. carbohydrate or lipid), has significant impact on an individual's growth, development, survival and fecundity (Joern and Behmer, 1997;Naya et al, 2007;van Huis et al, 2008). However, the role of post-ingestive resource processing and allocation is not clear (Boggs, 1992).…”
Section: Introductionmentioning
confidence: 99%